Low Threshold, Wide Dynamic Range, Tunable, All-Optical Self-Modulator Based on Fano Resonance and Out-of-Plane Coupling in a Slab Photonic Crystal with a Graphene Layer - Reza Asadi; Zhengbiao Ouyang (Journal of Nanotechnology)
We demonstrate an all-optical modulator based on self-modulation in a one-dimensional slab photonic crystal (PhC) by using optical Kerr nonlinearity of graphene and Fano resonance effect. It has been shown that the effect of Fano resonance in a one-dimensional slab PhC for intensity enhancement can provide low threshold (~1 MW/cm2), high frequency (>1 THz), and wide dynamic range (>3 THz) tunability for the all-optical self-modulator. Such a self-modulator can find applications in optical pulse generations, optical clocks, frequency shifting, and so forth.